Case reportTwo cases of trichoepithelioma - Czarniawska-Grzesińska, Małgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Trichoepitheliomas are benign skin tumours of hair follicle differentiation. They occur either in multiple lesions, transmitted as an autosomal dominant trait, known as epithelioma adenoides cysticum , or as a solitary lesion, which is not inherited. One of its forms is desmoplastic trichoepithelioma. Two cases of trichoepithelioma are presented. First, multiple trichoepithelioma in a young woman with extremely numerous lesions localized on the face, neck and ears, and the second solitary desmoplastic trichoepithelioma. Clinical and histopathological differentiation as well as therapeutic methods are discussed